2003
DOI: 10.1046/j.1460-9592.2003.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of remifentanil and fentanyl for fast track paediatric cardiac anaesthesia

Abstract: The remifentanil based anaesthetic was associated with a significantly slower HR than the fentanyl based anaesthetic. The clinical implications of the slower HR during remifentanil anaesthesia could be important and should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 14 publications
(16 reference statements)
0
23
0
1
Order By: Relevance
“…Severe bradycardia induced by remifentanil has been reported in numerous studies in adults [2][3][4] and in children [20][21][22]. In the overall analysis of the effects of remifentanil without atropine (REMI group), the lengthening of RR interval and the simultaneous increase of the HF component and rmssd suggested parasympathetic activation in the genesis of this bradycardia.…”
Section: Discussionmentioning
confidence: 89%
“…Severe bradycardia induced by remifentanil has been reported in numerous studies in adults [2][3][4] and in children [20][21][22]. In the overall analysis of the effects of remifentanil without atropine (REMI group), the lengthening of RR interval and the simultaneous increase of the HF component and rmssd suggested parasympathetic activation in the genesis of this bradycardia.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of fentanyl on sevoflurane, which has been shown to be interchangeable with remifentanil in children, has been documented. 5,6 There exists a 1:1.5 potency ratio between fentanyl and remifentanil. 7 Zhang et al have shown that in children aged five to ten, an increase in fentanyl serum levels from 0.62 ± 0.13 µg·L -1 to 1.51 ± 0.18 µg·L -1 produces a decrease in sevoflurane MAC from 1.03 ± 0.07% to 0.64 ± 0.01%.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In children, remifentanil and fentanyl have been shown to be interchangeable clinically. 5,6 Remifentanil has been shown to have superior recovery characteristics and is effective at dosages much lower than those required for other commonly-used opioids such as fentanyl. 7 The effect of remifentanil in reducing the minimum alveolar concentration MAC-BAR of sevoflurane has been demonstrated in adults.…”
mentioning
confidence: 99%
“…It was observed that 1 µg kg -1 min -1 remifentanil infusion and PCA fentanil bolus administration were effective for analgesia. Robert et al (11) used fast-track anaesthesia protocol with remifentanil and fentanyl in pediatric cases and did not found any difference between postoperative analgesic requirements.…”
Section: Discussionmentioning
confidence: 98%